A relatively common homozygous TRAPPC4 splicing variant is associated with an early-infantile neurodegenerative syndrome. - Ghosh, Shereen G; Scala, Marcello; Beetz, Christian; Helman, Guy; Stanley, Valentina; Yang, Xiaoxu; Breuss, Martin W; Mazaheri, Neda; Selim, Laila; Hadipour, Fatemeh; Pais, Lynn; Stutterd, Chloe A; et al. (Eur J Hum Genet, 2021)
Trafficking protein particle (TRAPP) complexes, which include the TRAPPC4 protein, regulate membrane trafficking between lipid organelles in a process termed vesicular tethering. TRAPPC4 was recently implicated in a recessive neurodevelopmental condition in four unrelated families due to a shared c.454+3A>G splice variant. Here, we report 23 patients from 17 independent families with an early-infantile-onset neurodegenerative presentation, where we also identified the homozygous variant hg38:11:119020256 A>G (NM_016146.5:c.454+3A>G) in TRAPPC4 through exome or genome sequencing. No other clinically relevant TRAPPC4 variants were identified among any of over 10,000 patients with neurodevelopmental conditions. We found the carrier frequency of TRAPPC4 c.454+3A>G was 2.4-5.4 per 10,000 healthy individuals. Affected individuals with the homozygous TRAPPC4 c.454+3A>G variant showed profound psychomotor delay, developmental regression, early-onset epilepsy, microcephaly and progressive spastic tetraplegia. Based upon RNA sequencing, the variant resulted in partial exon 3 skipping and generation of an aberrant transcript owing to use of a downstream cryptic splice donor site, predicting a premature stop codon and nonsense mediated decay. These data confirm the pathogenicity of the TRAPPC4 c.454+3A>G variant, and refine the clinical presentation of TRAPPC4-related encephalopathy.